APPLICATION OF LESSON STUDY TO IMPROVE THE TEACHING ABILITIES OF PPL STUDENTS AT UNIVERSITAS ISLAM MADURA IN MAN 2 PAMEKASAN - Jaftiyatur Rohaniah; Qiromah Qiromah; Ach Aldi Rofiqi; Suhaila Suhaila; Akh Rofiqi (Dewan Pendidikan Pamekasan, 2023)
This study aims to describe the learning activities of PPL students, Faculty of Teacher Training and Education, Madura Islamic University at MA Negeri Pamekasan using the lesson study method. Subject in this study is a student of the English Language Education study program, Faculty of Teacher Training and Education, Madura Islamic University. This type of research is Lesson Study-based Classroom Action Research (PTK) using a qualitative approach. Data collection was carried out by observation and implementation of activities for 2 months. This research is expected to provide benefits in the form of new experiences as professional teachers for students participating in English Language Education lesson study.